Phytochemical Analysis and Pharmaceutical Applications of Monoterpenoids Present in the Essential Oil of Boswellia sacra (Omani Luban) - Foziya Khan; Luay Rashan (Advances in Pharmacological and Pharmaceutical Sciences)
Due to its intricacy and long-term usefulness, traditional medicine continues to be practiced in several nations. Among the many medicinal plants found in the Dhofar region of Oman, the aromatic oleo-gum resin generated by Boswellia sacra, commonly referred to as frankincense, stands out for its medical and commercial significance. Resin-carrying ducts are unique to members of the Boswellia family. Boswellia sacra Flueck is one of the 29 species in the genus Boswellia (Burseraceae) and has long been cultivated for its aromatic gums and resins for use as incense. In addition to the resins (60%–80% alcohol soluble), gums (15%–20% water soluble), and essential oil (5%–7%), other components, including polysaccharides and polymeric compounds, also exist in smaller amounts. Physiochemical analyses indicate that Boswellia resin oil is made up of 42.5% diterpenes, 13.1% monoterpenes, and 1% sesquiterpenes. Traditional medicine makes extensive use of frankincense for the treatment of stomach diseases, Alzheimer’s disease, and hepatic illnesses. The bioactive chemicals present in frankincense, particularly boswellic acids, are plentiful. The current review examines various compounds present in different species of Boswellia, especially Boswellia sacra, along with their structure.